THE IMPLEMENTATION OF MATERIAL CRIMINAL LAW AGAINST CRIMINAL ACT OF EMBEZZLEMENT IN OFFICE - Abrahams, Deny; Amiq, Bahrul; Prawesthi, Wahyu; Khoidin, M. (jfpublisher, 2023)
The crime often committed is embezzlement, dishonesty by hiding other people's goods/assets by one or more people without the owner's permission to control or use it for other purposes. In Article 374 of the Criminal Code, the term embezzlement in the office can be said to be a crime of embezzlement with a weighting. The method used in this research is normative juridical research that examines or analyzes primary and secondary legal materials by understanding law as a set of rules or positive norms in the statutory system that regulates human life. Based on the research result, the application of material criminal law to cases of criminal embezzlement in the office is implemented based on legal facts, including the statements of witnesses, statements of the accused, letters, and the presence of evidence. Besides that, before the judge imposes a sentence, he needs to consider what can aggravate and mitigate the defendant to apply a sentence commensurate with the act and provide justice for the defendant and a deterrent effect against a decision.